The Impact of Fintech in the Performance of European Commercial Banks - Pires Frade, Marta (2024)
In the last decade, the financial sector has witnessed a constant evolution in the services it provides due to digitalization. Therefore, terminology financial technology, or Fintech, has become a common presence in the day-to-day of most population. With the emergence of these new financial technology companies, traditional institutions such as banks felt the pressure of competition through many outlines. Thus, the aim of this research is to comprehensively investigate and analyse the impact of Fintech on the performance of commercial banks, with a focus on key performance indicators such as profitability and efficiency. A total of 816 commercial banks from 20 European countries make up the study's sample. The period of analysis was from 2012 to 2021 and 202 Fintech companies founded during this period the number were considered relevant for the analysis. The study was performed using the GMM (Generalized Method of Moments) estimator and the main results show that the formation of fintech companies has a significant negative impact on bank’s profitability. Also, results show that returns of larger banks are more susceptible to the unfavourable effects of fintech creation, considering the size of the banks